A Systematic Review of Pain Management Barriers Among Arthralgia Patients - Mr. Rameshchandra B. Kaila (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
Pain management is a specific issue among nursing-home residents that provides major and unique problems to caregivers in terms of providing proper care. Over the past decade, the scope of this public health issue has been thoroughly documented. A person's perception and response to pain may be influenced by a variety of circumstances. Ethnic/cultural values, age, surroundings, and support system, as well as anxiety and stress, are all factors to consider. A stressful setting, such as a hospital or a nurse's attitude, might raise a patient's anxiety and reduce their pain tolerance. The present article is an attempt to examine a number of characteristics that have been identified as barriers to pain treatment in arthralgia patients.